Integrated systems biology to study non-alcoholic fatty liver disease in obese women - Hoyles,L; Fernández-Real,JM; Federici,M; Serino,M; Azalbert,V; Blasco,V; Abbott,J; Barton,RH; Puig,J; Xifra,G; Ricart,W; Woodbridge,M; et al. (2017)
Metagenomic (faecal microbiome), transcriptomic (liver biopsy), metabonomic (plasma and urine, 1H-NMR) and clinical (28 variables) data were collected for 56 morbidly obese (BMI >35) women from Italy (n = 31) and Spain (n = 25) who elected for bariatric surgery. Data were integrated to evaluate the contribution of the gut microbiome to the molecular phenome (hepatic transcriptome, plasma and urine metabonome) of NAFLD independent of clinical confounders (age, BMI, cohort) using partial Spearman’s correlation. NAFLD activity score (NAS) was anti-correlated with microbial gene richness, and correlated with abundance of Proteobacteria. KEGG analyses of metagenomic data suggested increased microbial processing of dietary lipids and amino acids, as well as endotoxin-related processes related to Proteobacteria. Metabonomic profiles highlighted imbalances in choline metabolism, branched-chain amino acid (BCAA) metabolism and gut-derived microbial metabolites resulting from metabolism of amino acids. NAFLD-associated hepatic transcriptomes were associated with BCAA metabolism, endoplasmic reticulum/phagosome, and immune responses associated with non-specific microbial infections. Molecular phenomic signatures were stable and predictive regardless of sample size, and consistent with the microbiome making a significant contribution to the NAFLD phenome. There is disruption of the gut– liver axis in NAFLD, which can be seen in the gut microbiome, hepatic transcriptome and urinary and plasma metabonomes. Consistency of phenome signatures strongly supports a relationship between microbial amino acid metabolism and microbial gene richness, hepatic gene expression and biofluid metabonomes, and ultimately NAS.